Global multidimensional poverty index 2023: Unstacking global poverty – Data for high-impact action - United Nations Development Programme (United Nations Development Programme (UNDP) and Oxford Poverty and Human Development Initiative (OPHI), 2023)
In 2015 the 2030 Agenda for Sustainable Development and Sustainable Development Goal (SDG) 1 set out to overcome the greatest global challenge: ending poverty in all its forms. At the midpoint to 2030, people’s lives continue to be battered in multiple ways simultaneously. Globally, an array of challenges impedes poverty reduction—widespread inequality, political instability and conflict, a climate emergency, COVID-19 pandemic recovery, and cost of living and other crises. There are both commonalities and specifics that cloud the way for each country. Measures of multidimensional poverty attempt to offer clear priorities for addressing poverty, going beyond monetary deprivations. The annual global Multidimensional Poverty Index (MPI), jointly published by the Human Development Report Office (HDRO) of the United Nations Development Programme and the Oxford Poverty and Human Development Initiative (OPHI) at the University of Oxford since 2010, measures interlinked deprivations in health, education and standard of living that directly affect a person’s life and wellbeing. The global MPI is the only counting-based index that measures overlapping deprivations for more than 100 countries and 1,200 subnational regions and offers a key perspective on SDG 1, while encompassing indicators related to other SDGs. The global MPI can be pictured as a stack of blocks, each of which represents a deprivation of a poor person. The goal is to eliminate deprivations so the height of the stack declines. This report presents a compact update on the state of multidimensional poverty (henceforth referred to as “poverty”) in the world. It compiles data from 110 developing countries covering 6.1 billion people, accounting for 92 percent of the population in developing countries. It tells an important and persistent story about how prevalent poverty is in the world and provides insights into the lives of poor people, their deprivations and how intense their poverty is—to inform and accelerate efforts to end poverty in all its forms. As still only a few countries have data from after the COVID-19 pandemic, the report urgently calls for updated multidimensional poverty data (box 1). And while providing a sobering annual stock take of global poverty, the report also highlights examples of success in every region.